The Integrity of Legal Principles and Sharia Values in Designing Goods Deposit Contracts from an Indonesian Legal Perspective - Faza Aulia Syahreini; Muhammad Bagus Anshary Sinanga; Bunga Putri Ayu Nasution; Putri Syakillah; Muhammad Ikhlas Bin Rosele Lubis (ISNU Sumatera Utara, 2025)
The design of a goods custody contract is an important aspect of civil and sharia law, which encompasses the principle of integrity in legal relations in Indonesia. This study analyzes how goods custody contracts can be structured to not only comply with civil law provisions but also align with sharia values. By considering the principles of fairness, clarity, and mutual benefit, an ideal contract design is expected to overcome potential conflicts between the two legal systems. Through normative research methods and comparative analysis, it is explained that integrating civil and sharia law in goods custody contracts can increase trust between the parties involved, create transparency in transactions, and encourage sustainable economic growth in accordance with sharia principles. This research is expected to contribute to the formation of a more comprehensive regulatory framework in the context of the sharia economy in Indonesia.